The original figure plates of "A new fossil species of the reticulated beetle genus Cupes (Coleoptera: Archostemata: Cupedidae) from Eocene Baltic amber" - Shuhei Yamamoto (6421775) (2025)
The original figure plates of "A new fossil species of the reticulated beetle genus Cupes (Coleoptera: Archostemata: Cupedidae) from Eocene Baltic amber" published in Zootaxa. Yamamoto, S. (2024) A new fossil species of the reticulated beetle genus Cupes (Coleoptera: Archostemata: Cupedidae) from Eocene Baltic amber. Zootaxa, 5432(4): 451–460. (doi: 10.11646/ZOOTAXA.5432.4.1). https://www.mapress.com/zt/article/view/zootaxa.5432.4.1 https://doi.org/10.11646/ZOOTAXA.5432.4.1 Abstract The single extant species of the reticulated beetle genus Cupes Fabricius is confined to North America. In contrast, a diverse and abundant fossil record of the genus has been documented in Cenozoic deposits in Europe, especially in Eocene Baltic amber. This paper describes another species, Cupes balticus sp. n., as the eighth named species of the genus from Baltic amber. The discovery of an additional Cupes species further evidences the hidden paleodiversity of reticulated beetles in European Eocene forests.